2021
DOI: 10.3390/healthcare9091167
|View full text |Cite
|
Sign up to set email alerts
|

Research on Urban Medical and Health Services Efficiency and Its Spatial Correlation in China: Based on Panel Data of 13 Cities in Jiangsu Province

Abstract: The improvement of the efficiency of medical and health services is of great significance for improving the high-quality and efficient medical and health services system and meeting the increasingly diverse health needs of residents. Based on the panel data of 13 cities in Jiangsu Province, this research analyzed the relative effectiveness of medical and health services from 2015 to 2019 using the super efficiency slack-based measure-data envelopment analysis model, and the Malmquist index method was used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…In terms of efficiency evaluation, SE-SBM-DEA is mainly used to evaluate the relative performance of medical institutions at all levels in a certain period of time, which cannot continuously compare different periods ( 34 , 35 ). It is also important to investigate the dynamic development of efficiency for medical institutions at all levels over a while.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of efficiency evaluation, SE-SBM-DEA is mainly used to evaluate the relative performance of medical institutions at all levels in a certain period of time, which cannot continuously compare different periods ( 34 , 35 ). It is also important to investigate the dynamic development of efficiency for medical institutions at all levels over a while.…”
Section: Methodsmentioning
confidence: 99%
“…The focus of research on the dynamics of health service networks lies in inter-regional coordination and the optimal allocation of resources, aiming to enhance the e ciency and overall quality of health services (Lin et al, 2021). Although cross-sectional studies primarily focus on the immediate state of resource distribution, broader research has revealed the spatial spillover effects of health system e ciency, and by assessing the spatial clustering patterns of healthcare facilities, the rationality of the existing healthcare systems has been evaluated, thereby highlighting the necessity of optimising resource allocation strategies (Wang & Nie, 2019;Yang et al, 2022).…”
Section: Resource Flow Network and Equity Of Health Servicesmentioning
confidence: 99%
“…Management issues concerning individuals and organizations are integral to the research field of public health. By effectively utilizing health informatics techniques, valuable information can be extracted to provide deeper insights that support informed decision making [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: The Organization Of This Special Issuementioning
confidence: 99%